Impalement brain injury from steel rod causing injury to jugular bulb: Case report and review of the literature. (November 2014) - Grossbach, Andrew J.; Abel, Taylor J.; Smietana, Janel; Dahdaleh, Nader; Severson, Meryl A.; Hasan, David
Abstract Background: The management of impalement penetrating brain injuries (IPBI) from non-missile objects is extremely challenging, especially when vascular structures are involved. Cerebral angiography is a crucial tool in initial evaluation to assess for vascular injury as standard non-invasive imaging modalities are limited by foreign body artifact, especially for metallic objects. Case study: This study reports a case of an IPBI caused by a segment of steel rebar resulting in injury to the left jugular bulb and posterior temporal lobe. It describes the initial presentation, radiology, management and outcome in this patient and reviews the literature of similar injuries.